Effect of different inoculations on biogas and methane production through anaerobia biodigeston using residues from the avícola sector - Bortolini, Joseane (2022)
The present study aimed to analyze the use of different digestates as inocula for the anaerobic digestion of poultry litter, evaluating the biogas and methane production. The inocula used were: bovine and porcine biofertilizer; with feeding loads of 0.67, 1.00 and 1.67 gVS L-1 day-1. Statistical analyses followed a split-plot design, where the main plot being inoculum and the feeding load as secondary. The experimental data were submitted to analysis of variance, at the level of 5% of significance. The following variable responses were considered: biogas production, specific biogas production as a function of volatile solids (VS) added to the biodigester, specific biogas production as a function of organic load, in terms of COD, and methane production. The highest rates of average biogas production, specific biogas production by VS added, specific production of biogas as a function of COD, and average methane production occurred with the use of bovine inoculum. Through the analysis of the total average percentage of methane production, productions of 63.0% and 54.5% for bovine and swine inoculum. Considering the results obtained, the use of bovine inoculum for the process of anaerobic digestion of poultry litter is recommended vinculado a produção de biogás e metano.